Managing Nutritional Needs and Health Status of Children in Communities Affected by Natural Disasters - Susilo Wirawan (Miracle Journal Get Press, 2026)
Natural disasters significantly impact food security, parenting practices, and children's nutritional status, particularly in the post-disaster phase, which is characterized by limited access to food and health services. This study aims to analyze the relationship between household food security and child nutritional management with the nutritional status of toddlers in disaster-affected communities. The study used a descriptive analytical design with a cross-sectional approach in 120 households with toddlers aged 0–59 months. Data were collected through structured interviews and anthropometric measurements, then analyzed using the chi-square test to assess the relationship between variables. The study results show that the majority of households are vulnerable to food insecurity and have adequate to inadequate child nutrition management. Household food security is significantly associated with toddler nutritional status based on indicators of weight for age (W/A), height for age (H/A), and weight for height (W/H). Toddlers from food insecure households are at higher risk of malnutrition, stunting, and wasting. Furthermore, inadequate management of children's nutritional needs is also significantly associated with all indicators of nutritional status disorders. This study concludes that post-disaster nutritional status of toddlers is a multidimensional outcome influenced simultaneously by structural and behavioral family factors. Therefore, post-disaster nutrition interventions need to integrate strengthening household food security with assistance in family- and community-based nutrition management to support sustainable child nutritional recovery.